Piezo1 induced apoptosis of type II pneumocytes during ARDS - Liang, Guo-Peng; Xu, Jing; Cao, Li-li; Zeng, Yi-Hua; Chen, Bai-Xu; Yang, Jing; Zhang, Zhong-Wei; Kang, Yan (Respiratory research, 2019)
The mechanisms of lung injury in acute respiratory distress syndrome (ARDS) are not well understood.Piezo1 was recently identified as a mechanotransduction protein. The present study found the expression of Piezo1 in type II pneumocytes and investigated its role in mediating ARDS-related lung injury. Sprague-Dawley rats were used to establish an ARDS model, the expression of Piezo1,lung injuries, apoptosis as well as calcium influx were assessed. Piezo1 was expressed in type II pneumocytes as shown by immunofluorescence staining and expression was increased in the ARDS model. Knockdown of Piezo1 reduced apoptosis which was related to the elevation of Bcl-2.Calcium influx played a vital role in Piezo1-induced apoptosis. Piezo1 was expressed in type II pneumocytes. Mechanical stretch of alveoli during ARDS induced activation of the Piezo1 channel,which resulted in calcium influx. The increased intracellular Ca2+ induced the apoptosis of type II pneumocytes, which may be related to the Bcl-2 pathway.